Contextual Factors Associated with Burnout among Chinese Primary Care Providers: A Multilevel Analysis - Li, Huiwen (Int J Environ Res Public Health, 2019)
Burnout is a common and growing phenomenon in the health care setting. The objective of the present study is to examine contextual factors in the workplace associated with burnout among primary care providers (PCPs) in Shandong Province, China. A cross-sectional survey was conducted among 951 PCPs nested within 48 primary health institutions (PHIs). Burnout was measured using the Maslach Burnout Inventory–Human Services Survey (MBI–HSS). We used two-level random intercept linear regression models to examine individual- versus workplace-level risk factors for burnout. The result revealed that 33.12%, 8.83% and 41.43% PCPs were experiencing a high degree of emotional exhaustion (EE), depersonalization (DP) and low personal accomplishment (PA). In multilevel analysis, the most significant and common individual-level predictors of burnout were lack of perceived work support and autonomy. At the institutional level, workload was positively related to EE (odds ratio (OR): 6.59; 95% confidence interval (CI): 3.46–9.72), while work support was related to higher PA (OR: 3.49; 95% CI: 0.81–6.17). Greater attention should be paid to the influence of the work environment factors (workload and work support) to prevent burnout. Strategies such as increasing human resources allocated to PHIs and establishing a supportive work environment are encouraged to prevent and reduce burnout among PCPs in China.